The Identification of "Author" and "Addressee" in the Discourse of the Representative of Volga Germans of Siberia; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Kostomarov P. I. Petr Ivanovich (2015, 2015)
Title screen